Comparative Study Between Mixed Model Assembly Line And Flexible Assembly Line Based On Cost Minimization Approach [TS167. F278 2008 f rb]. - Fawad Ahmed, Fawad Ahmed (2008)
Mixed Model Assembly Line are widely used to produce different models as per customer's demands.